Трактография головного мозга при сахарном диабете и когнитивных нарушениях - Самойлова Ю. Г. Юлия Геннадьевна; Матвеева М. В. Марина Владимировна; Тонких О. С. Ольга Сергеевна; Кудлай Д. А. Дмитрий Анатольевич; Олейник О. А. Оксана Алексеевна; Фимушкина Н. Ю. Наталья Юрьевна; Гергет О. М. Ольга Михайловна; Борисова А. А. Алена Александровна (2020, 2020)
Заглавие с экрана